The Second Phase of the Trypillia Mega-Site Methodological Revolution: A New Research Agenda. (21st July 2014) - Chapman, John; Videiko, Mikhail Yu; Hale, Duncan; Gaydarska, Bisserka; Burdo, Natalia; Rassmann, Knut; Mischka, Carsten; Müller, Johannes; Korvin-Piotrovskiy, Aleksey; Kruts, Volodymyr
<x content-type="archive" xml:space="preserve">Abstract</x> The first phase of the Trypillia mega-sites' methodological revolution began in 1971 with aerial photography, magnetic prospection, and archaeological excavations of huge settlements of hundreds of hectares belonging to the Trypillia culture in Ukraine. Since 2009, we have created a second phase of the methodological revolution in studies of Trypillia mega-sites, which has provided more significant advances in our understanding of these large sites than any other single research development in the last three decades, thanks partly to the participation of joint Ukrainian-foreign teams. In this paper, we outline the main aspects of the second phase, using examples from the Anglo-Ukrainian project 'Early urbanism in prehistoric Europe: the case of the Trypillia mega-sites', working at Nebelivka (also spelled 'Nebilivka'), and the Ukrainian-German project 'Economy, demography and social space of Trypillia mega-sites', working at Taljanky ('Talianki'), Maydanetske ('Maydanetskoe'), and Dobrovody, as well as the smaller site at Apolianka.